DECLINE AND COLLAPSE OF THE ABBASID DYNASTY - Fitri, Dina; M, Afrizal (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2024)
The purpose of this writing is to describe the causes of the decline that resulted in the destruction of the Abbasid dynasty. The focus of the discussion in the writing is to review in more depth both internal and external factors. The research method used is descriptive qualitative using a library research approach by taking relevant sources from books and journal articles. The results of the research obtained are the conditions during the reign of the Abbasid Dynasty. Data collection techniques are carried out through literature studies by collecting primary and secondary data that are relevant to the topic of the Abbasid Dynasty including aspects of its decline and destruction. The decline and destruction of the Abbasid Dynasty were caused by several internal and external factors. In essence, these factors of decline were already visible in the first period, but because the caliph at that time was strong, it could not develop. As for internal factors came from within the caliphate, namely starting from the establishment of the Abbasid Dynasty in collaboration with the Persians so that there was a struggle for power that prioritized each nation, the weakness of the caliph so that he was unable to stem the establishment of small dynasties within the caliphate and the caliph was only a symbol, the formation of small dynasties was also caused by divisions between beliefs in the dynasty, namely the debate between Shiites and Ahlussunnah and the debate about the Qur'an being qadim or hadith. As for external factors, namely the existence of the crusades and attacks from the Mongols which resulted in the destruction of the Abbasid Dynasty. The destruction of the Abbasid dynasty certainly had an impact on the Islamic world later, both in terms of science, politics and economy.